A Slippery Slope When Using an Evidence-Based Intervention Out of Context. How Professionals Perceive and Navigate the Fidelity-Adaptation Dilemma—A Qualitative Study - Zetterlund, Johanna; von Thiele Schwarz, Ulrica; Hasson, Henna; Neher, Margit (Frontiers in Health Services, 2022)
Adaptations are often necessary to effectively translate evidence-based interventions (EBI) between contexts, but compliance with the EBIs’ core components is still important, which is referred to as the fidelity–adaptation dilemma. In the sustainment phase of implementation, it is the professionals delivering the EBIs who are tasked with the decision-making regarding adaptations, but the currently used models and frameworks mostly focus on the initial phases of implementation. To better understand and guide professionals in using EBIs, there is a need to explore professionals’ perceptions of the fidelity–adaptation dilemma. The aim of this study is consequently to explore how professionals perceive and navigate the fidelity–adaptation dilemma when using an EBI out of context. Semi-structured interviews were held with 19 psychologists working in primary care. The interviews concerned EBIs in general and Cool Kids, an evidence-based parenting education program designed for children with anxiety that is now used for children with lower levels of anxiety in another setting. The data were analyzed using an inductive content analysis method and the analysis resulted in two themes: My standpoint regarding fidelity and adaptation is clear and Managing fidelity and adaptations is complicated. The first theme summarizes the professionals’ perceptions of confidence for either favoring fidelity or adaptations, as well as reasons for why they made adaptations. For the second theme, the professionals expressed concern about sometimes meeting difficulties with the dilemma when following their original inclination and having second thoughts about the impact the adaptations have in practice. The professionals generally had strong preferences regarding fidelity and adaptations, but neither preference prevented them from facing difficulties with the dilemma. The results point to a need for better information about possible adaptations from developers but also better support and guidance for professionals when implementing EBIs to ensure quality implementation and facilitate implementation. The results of this study can inform the design of support for professionals in managing the dilemma.